Physical activity & depressive symptoms among overweight & obese pregnant women in Terengganu - Suan, W.B.; Marhazlina, M.; Rosliza, Y.; Lin, L.P; Ain Widad, A. (2021)
Introduction: Depression during pregnancy would affect not only the mother but also the child's development. The prevalence of depression during pregnancy in Malaysia has increased from 8.3% to 12.2% in 2018. It is presumed that exercise and physical activity prevent depression and decrease depressive symptoms by altering neurotransmitter and depression-related hormone levels. Objective: To evaluate the association between physical activity and depressive symptoms score among overweight and obese pregnant women in Terengganu. Methodology: A total of 26 pregnant women (n=14 overweight and n=12 obese) in their second and third trimester who registered in health clinics in Terengganu. aged ranging from 22 to 41 years completed this study. This cross-sectional study used self-administered questionnaires consisting of socio-demographic characteristics, Pregnancy Physical Activity Questionnaires (PPAQ-Malay) and Edinburgh Postpartum Depression Scale (EPDS-Malay). The data were analysed by using IBM SPSS version 23. Results: Majority of the participants working in government sectors (61.5%, n=16), with monthly income range from RM1001-RM3000 (42.3%. n=11). More than half of the participants (61.5%, n=16) were in their third trimester. Most of the participants participated in right-intensity activity (18-1±11.5 MET-hr/week) in the form of occupational type (42.2%,50.6140.8 MET-hr/week) while 31.5% were in inactivity category (37.7e28.3 MET-hr/week) 15.4% (n=4) of them have an EPOS score of more than 10 which signifies depressive symptoms. There was a fair positive correlation between physical activity and depression symptoms score (r=0.469, p=0.016). Conclusion: Physical activity is related to depressive symptoms among overweight and obese pregnant women in Terengganu. Appropriate measures should be taken to increase awareness and reduce depressive symptoms risk during pregnancy.